Efektifitas Bekam dan Akupuntur dalam Menurunkan Intensitas Nyeri pada Lansia dengan Kecurigaan Osteoarthritis - I Dewa Made Ruspawan; I Ketut Sudiantara; I Gusti Ketut Gede Ngurah; I Wayan Suardana (Jurnal Gema Keperawatan, 2016)
This study aims to determine the effectiveness of acupuncture and cupping in reducing the intensity of pain in OA clients. This research was conducted with quasy design experiment, equivalent pre and post test control group. The study was conducted in Latu Usada With acupuncture and cupping until each 32.The pain metode use numeric scale pain. Results Showed a mean age of 64 years subject OA clients, the majority of men with primary education with the largest job as a farmer. OA pain mostly occurred in the waist and knees with a distribution of 40.6% and 43.8%. 4 pain scale before the intervention, after the intervention, after the intervention of the subject acupuncture pain scale pd 2, while the subject of cupping 3. The results of the analysis found that Acupuncture and Cupping were able to reduce pain significantly respectively p= 0.00 (p 0.05. ). Results of the analysis of different test found that acupuncture is more effective in reducing pain in clients with OA with p= 0.00 ( 0.05 ). CI 95% ( 0431-1256 ). Cupping and acupuncture can produce substance that can reduce pain through the mechanism of the HPA axis and gate control system. Using Acupuncture is better as it can directly reach the target more quickly.